CONCEPTUAL MAPPING OF CORPORATE SOCIAL RESPONSIBILITY IN THE CONTEXT OF SUSTAINABILITY - Susanto, Putu Chris (Journal of Human Capital Development (JHCD), 2025)
ABSTRACT The concept of corporate social responsibility (CSR) relates to stakeholder theory, as it seeks to align corporate decision-making and actions with the interests of all stakeholders. Along with the development of the CSR concept, derivative concepts including corporate social innovation (CSI) and creating shared value (CSV) have emerged, with a distinct focus on sustainability. In this study, a thematic analysis through a bibliometric study was conducted on the most prominent CSR-related keywords from 941 scientific articles published in reputable international journals between 2013 and 2022. Subsequently, a conceptual map pertaining to CSR, CSI, and CSV concepts in the context of sustainability was developed. The conceptual map depicts CSR as the main concept encompassing CSI and CSV (since both concepts were developed from the criticisms and limitations of CSR). The conceptual map shows that CSR, CSI, and CSV are formed by certain theories, assumptions, and concepts. CSR is supported by four underlying concepts, i.e., stakeholder theory, legitimacy theory, Carroll’s pyramid, and the triple bottom line. CSI is built upon the underlying concepts of strategic innovation and resource-based view (RBV), while CSV is constructed by the three levels of shared value and social exchange theory. Ultimately, the conceptual map shows sustainability as the culmination of the CSR, CSI, and CSV concepts. This study uniquely utilizes bibliometric and thematic analyses to map the relationship between CSR, CSI, and CSV to sustainability, offering insights for academics and practitioners seeking to integrate social responsibility with their core business strategies for sustainability. Keywords: conceptual map, CSR, CSI, CSV, sustainability